Associations Between Taq1A/C957T Polymorphic Variants and Autonomic Responsivity in a Slot Machine Task: Influence of Real-Life Gambling Exposure and Sex - Hultman, Cathrine; Rehn, Mattias; Sescousse, Guillaume; Nilsson, Kent; Vadlin, Sofia; Åslund, Cecilia (Journal of gambling studies, 2025)
Monetary reward processing during gambling is associated with dopaminergic functioning. Emotional reactivity to different gambling stimuli can be indexed by autonomic nervous system (ANS) responses measured by skin conductance responses (SCR) and heart rate (HR). Genetic markers regulating neural dopaminergic activity, such as the D2 dopamine receptor, might confer differential sensitivity to gambling stimuli, which may also be modulated by previous exposure to gambling. To date, no previous studies have explored the relationship between genetic markers of the D2 dopamine receptor, real-life gambling exposure and ANS responses during gambling. Hence, this study explored associations and interactions between DRD2 C957T (rs6277) and ANKK1 Taq1A (rs1800497) genotypes, real-life gambling frequency and autonomic responses during reward anticipation and outcome delivery in a slot machine task producing wins, near-misses and full-misses. Participants ( n = 270) performed a computerized slot machine task with recordings of SCRs and HR responses during gambling performance and provided saliva samples for DNA extraction. Taq1A A1 carriers showed increased SCRs and HR responses during reward anticipation and to wins. Greater responsivity during anticipation, as well as to wins and full-misses, was also observed in C957T heterozygotes. Regarding real-life gambling involvement, higher gambling frequency among Taq1A A1 carriers was associated with decreased HR responses during anticipation and to wins. Results suggest that polymorphic variants of the D2 dopamine receptor may confer differential sensitivity to different gambling stimuli which may further be modulated by real-life gambling exposures. However, further studies are needed in well powered samples of gamblers and control subjects.